Unified 1.9…4.0 MeV linear accelerators with interchangeable accelerating structures for customs inspection - Budtov, A.A.; Klinov, A.P.; Krestianinov, A.S.; Ryabtsov, A.V.; Udovichenko, S.Yu. (Вопросы атомной науки и техники, 2004)
A series of compact linear electron accelerators for 1.9, 2.5 and 4.0 MeV equipped with a local radiation shielding has been designed and constructed in the NPK LUTS, the D.V. Efremov Institute (NIIEFA). The accelerators are intended for mobile facilities used for customs inspection of large-scale containers. Results of optimizing calculations of irradiator parameters and electron dynamics, verified under accelerators’ testing, are presented in the report. The main design approaches allowing the construction of unified accelerators with interchangeable accelerating structures for energies in the range of 1.9…4.0 MeV are also given.